(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to identify the impact of a proposed training program based on artificial intelligence applications to develop digital skills among science teachers at the primary stage and its impact on developing future thinking among their students. To achieve this goal, two approaches were used: the descriptive and analytical approaches, which were used to identify the training needs necessary to develop digital skills among science teachers in the primary stage and to prepare a list of artificial intelligence applications and a list of digital skills. The experimental approach with a quasi-experimental design, which reached 20 science teachers in the primary stage in the city of Buraidah, affiliated with the General Administration of Education in the Qassim region, and the same pre-post measurement for the experimental and control groups of the student sample, which reached 120 students from the sixth grade of primary school in the city of Buraidah, were divided into two groups: 60 students as the experimental group and 60 students as the control group. The results of the search revealed that there are statistically significant differences at the level of significance (0.05) between the mean scores of the pre- and post-application. This is for the observation card of digital skills for science teachers at the primary stage, in favor of the post-application. There are statistically significant differences at the level of significance (0.05) between the mean scores of the pre- and post-application of the digital skills test for science teachers at the primary stage, in favor of the post-application, as well as statistically significant differences at the level of significance (0.05) between the mean scores of students in the experimental and control groups in the post-application of testing future thinking skills among primary school students, in favor of the experimental group. In light of these results, some recommendations and suggestions were presented